DEAD-box RNA helicase 21 interacts with porcine circovirus type 2 Cap protein and facilitates viral replication - Zhou, Jianwei; Zhao, Jie; Sun, Haoyu; Dai, Beining; Zhu, Ning; Dai, Qianhong; Qiu, Yonghui; Wang, Dedong; Cui, Yongqiu; Guo, Jinshuo; Feng, Xufei; Hou, Lei; et al. (Frontiers in Microbiology, 2024)
Porcine circovirus type 2 (PCV2) is the etiological agent of PCV2-associated diseases that pose a serious threat to the swine industry. PCV2 capsid (Cap) protein has been shown to interact with DEADbox RNA helicase 21 (DDX21), an important protein that regulates RNA virus replication. However, whether the interaction between DDX21 and the PCV2 Cap regulates PCV2 replication remains unclear. Herein, by using western blotting, interaction assays, and knockdown analysis, we found that PCV2 infection induced the cytoplasmic relocation of DDX21 from the nucleolus in cultured PK-15 cells. Moreover, the nuclear localization signal (NLS) of PCV2 Cap interacted directly with DDX21. The NLS of PCV2 Cap and 763 GSRSNRFQNK 772 residues at the C-terminal domain (CTD) of DDX21 were essential for the dual interaction. Upon shRNA-mediated DDX21 depletion in PK-15 cells, we observed impaired PCV2 replication via a lentivirus-delivered system, as evidenced by decreased levels of viral protein expression and virus production. In contrast, the replication of PCV2 increased in transiently DDX21-overexpressing cells. Our results indicate that DDX21 interacts with PCV2 Cap and plays a crucial role in virus replication. These results provide a reference for developing novel potential targets for prevention and control of PCV2 infection.